JUAL BELI ONLINE DROPSHIPPING DALAM PERSPEKTIF MAQASHID SYARI’AH - Tektona, Rahmadi Indra (IAIN Tulungagung, 2021)
Buying and selling which are conducted in muamalah form must hold on to the principles of Islamic law. Concomitant to technological developments, buying and selling also has developed by arise of online marketing. Online marketing allowed in islam as buying and selling conventionally. In online marketing, there is dropshipping system, which is the seller (dropshipper) can sells goods belongs to supplier by uploading images of the goods via internet. Dropshipping in an online marketing has weaknesses, so to minimize these weaknesses, in practice of dropshipping must be in accordance with maqashid syari'ah, which aims for the benefit. Dropshipping in an online marketing conducted through 2 (two) contracts are salam contract which is a contract between the seller (dropshipper) with the buyer, and wakalah contract which is a contract between the seller (dropshipper) with the supplier.